Proceedings of the 2017 2nd International Conference on Materials Science, Machinery and Energy Engineering (MSMEE 2017) 2017
DOI: 10.2991/msmee-17.2017.239
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of UV Curable Complex System Based on Vinyl Resin and Polyurethane Acrylate Prepolymer

Abstract: A UV curable complex system with vinyl resin and polyurethane acrylate photo-polymerization was investigated. The UV curing process of complex system was traced by IR. Thermal decomposition temperature of UV cured film for various system were determined by thermogravimetric analysis(TGA). And physical properties of those curing films were analyzed and compared. The results show The results show the thermal decomposition temperature, and alkali resistance and hardness of the product gradually decreased with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The highest T d within a temperature range of 410–490 °C can be ascribed to the decomposition of the cured TPGDA network. It has been reported that the T d of the UV-cured vinyl resin was approximately 425 °C, which is in the decomposition temperature range of 400–490 °C. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest T d within a temperature range of 410–490 °C can be ascribed to the decomposition of the cured TPGDA network. It has been reported that the T d of the UV-cured vinyl resin was approximately 425 °C, which is in the decomposition temperature range of 400–490 °C. , …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the T d of the UV-cured vinyl resin was approximately 425 °C, which is in the decomposition temperature range of 400−490 °C. 65,68 It is known that the curing efficiency can be described by thermal information in terms of changing exothermic characteristics and T g . 69,70 To observe the effect of curing time as well as the conversion degree on crystallization, the DSC thermograms of the UV LED-cured suPLA-TPGDA at different curing times were measured.…”
Section: Acs Sustainablementioning
confidence: 99%